Parents-Teacher Assisting Monitoring Application (PTAMA) System - Nor Syahidatul Nadiah, Ismail; Muhammad Nazrin, Kamaruddin; Nor Saradatul Akmar, Zulkifli; Syazana Syahirah, Jamaluddin (IEEE Xplore, 2019)
Education is an essential element in our life in order to build a better future for young generations. A school must have a better communication platform between teachers and parents to ensure collaboration in monitoring the children’s education. Due to time confinement and restrictive schedule, parents nowadays are not able to monitor their children’s progress accordingly in terms of school activities and student’s performance. Furthermore, instruction from the teachers toward the parents were not delivered properly. These are caused by multiple factors such as the inability to deliver messages correctly due to young age. Therefore, this paper proposes online Parent-Teacher Assisting Monitoring Application (PTAMA) system. The PTAMA system will be built in web based and mobile application system. There are five features in PTAMA system involve attendance, announcements, homework, feedback and letters. In this system, student’s attendance is recorded using Quick Response (QR) Code that is printed into student matric card. This system is specifically designed for primary school students. Rapid Application Development (RAD) cycle is chosen as a methodology to develop this PTAMA system. By having this PTAMA system, parents and teachers can collaborate to monitor the students’ performance